Why are we not exploring the potential of lower limb muscle power to identify people with sarcopenia? - Coelho-Júnior, Hélio José; Álvarez-Bustos, Alejandro; Landi, Francesco; da Silva Aguiar, Samuel; Rodriguez-Mañas, Leocadio; Marzetti, Emanuele (Ageing research reviews, 2025)
Sarcopenia refers to a neuromuscular disease characterized by age-related declines in muscle mass and function. Since Professor Rosenberg first introduced the concept of sarcopenia in 1989, numerous operational paradigms have been proposed, tested, and validated against negative outcomes. The most recent recommendations advocate that dynapenia, or reduced of muscle strength, should be used alongside low muscle mass for the identification of sarcopenia. This approach is based on the understanding that impairments in muscle strength are a major consequence of muscle failure. However, empirical evidence has yielded conflicting results regarding the ability of current sarcopenia definitions to identify individuals at higher risk of adverse health-related events. Muscle power — the capacity to generate strength rapidly — has emerged as a critical domain of physical performance in old age. Not only does it decline earlier and more drastically than other measures (e.g., muscle strength), but it is also more strongly associated with adverse outcomes. In this view point, we provide an appraisal of muscle power as a more reliable indicator of muscle failure, compared with other measures (e.g., strength), for identifying individuals with sarcopenia in both geriatric and non-geriatric settings. We also discuss major challenges hindering the conduct of meaningful investigations on this subject. •Impairments in muscle strength are seen as a major consequence of muscle failure;•The ability of current operationalization methods to identify sarcopenia is still inconclusive;•Muscle power is a critical determinant of physical performance;•Muscle power is more associated with negative outcome than muscle strength;•The potential of muscle power in identifying individuals with sarcopenia deserves to be explored.